Implementasi Undang - Undang No. 37 Tahun 2004 Tentang Kepailitan : Analisis Yuridis Terhadap Efektivitas Penyelesaian Utang Piutang di Indonesia - Amiliya Tul Laila; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Background: Bankruptcy represents a strategic legal institution for resolving complex debt and credit problems in Indonesia. Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations has been implemented for almost two decades, yet continues to face various challenges in practice. Objective: This research aims to analyze the effectiveness of bankruptcy law implementation in Indonesia, identify problematic issues in its application, and formulate recommendations for improving the national bankruptcy legal system. Method: This research employs normative juridical methods with descriptive analytical approaches. Primary data were obtained through interviews with legal practitioners, curators, and commercial court judges. Secondary data were collected from literature studies, court decision analysis, and comparative legal studies with other countries. Results: The implementation of Law No. 37/2004 still faces significant obstacles, including: (1) unclear minimum requirements for bankruptcy filing causing inconsistent court decisions; (2) insufficient PKPU timeframe that proves ineffective for restructuring; (3) diverse curator competencies affecting the quality of bankrupt estate management; (4) weak commercial court supervision over curator performance; and (5) minimal socialization of bankruptcy law to the public. Conclusion: Bankruptcy law reform is necessary through regulatory improvements, human resource capacity enhancement, and strengthening of supervisory systems to create an effective and equitable bankruptcy system.